Hubungan Kepemimpinan Transformasional Stres Kerja terhadap Kepuasan Kerja Perawat Ruang Rawat Inap Rumah Sakit Embung Fatimah Kota Batam Tahun 2024 - Rathia Ulfa; Nelli Roza; Rurry Nindya Taluphyta; Inke Asmika (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
According to Global data, the level of job satisfaction is at its lowest point, only (22%) workers worldwide are satisfied. In 2023, Japan was recorded as having job satisfaction (42%), and Portugal was reported to have one of the lowest satisfaction levels in Europe, especially among workers, and in Indonesia in 2014 according to the National Statistics Agency, 73% of employees were dissatisfied with their jobs. Several studies show that job satisfaction is still in the suboptimal category. This study aims to determine the relationship between transformational leadership and job stress on job satisfaction of inpatient nurses at Embung Fatimah Hospital, Batam City in 2024. This study uses a quantitative analytical design with a Cross Sectional approach to 83 inpatient nurses at Embung Fatimah Hospital, Batam City in 2024. Sampling uses the total sampling technique. The measuring instrument in this study uses a questionnaire. The results obtained transformational leadership in the good category as many as 61 nurses (47.7%), stress in the stress category as many as 45 nurses (35.2%) and job satisfaction in the satisfied category as many as 79 nurses (61.7%). Data analysis used is the sci square test. The test results obtained a p value of 0.001 <0.05 which means H0 is rejected and Ha is accepted. So it can be concluded that there is a significant relationship between transformational leadership and job stress on nurse job satisfaction in the Inpatient Room at Embung Fatimah Hospital, Batam City in 2024. Hospital management can maximize leaders by paying attention to nurse satisfaction such as providing promotions, salaries and coworkers according to expectations, especially for nurses in order to create optimal satisfaction.